1993
DOI: 10.1093/glycob/3.2.137
|View full text |Cite
|
Sign up to set email alerts
|

Differential distribution of major gangliosides in rat central nervous system detected by specific monoclonal antibodies

Abstract: We investigated the localization of major gangliosides in adult rat brain by an immunofluorescence technique with mouse monoclonal antibodies (MAbs). Five MAbs (GMB16, GMR17, GGR12, GMR5 and GMR13) that specifically recognize gangliosides GM1, GD1a, GD1b, GT1b and GQ1b, respectively, were used. We have found that there is a cell type-specific expression of the ganglioside in the rat central nervous system. In cerebellar cortex, GM1 was expressed in myelin and some glial cells. GD1a was detected exclusively in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
88
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(94 citation statements)
references
References 0 publications
6
88
0
Order By: Relevance
“…For example, ganglioside GM1 is widely distributed throughout the peripheral nervous system and has regulatory roles during neurogenesis and regeneration of injured peripheral nerves (OgawaGoto et al, 1992;Stojiljkovic et al, 1996). Ganglioside GT1b is expressed in the synapses of the brain (Kotani et al, 1993). Exposure of the neurons to ganglioside GT1b for 3 days drastically enhances actin-rich dendrite generation (Higashi and Chen, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…For example, ganglioside GM1 is widely distributed throughout the peripheral nervous system and has regulatory roles during neurogenesis and regeneration of injured peripheral nerves (OgawaGoto et al, 1992;Stojiljkovic et al, 1996). Ganglioside GT1b is expressed in the synapses of the brain (Kotani et al, 1993). Exposure of the neurons to ganglioside GT1b for 3 days drastically enhances actin-rich dendrite generation (Higashi and Chen, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…25 A large number of gangliosides have been isolated from the brains of various organisms, but only four structures, GM1, GD1a, GD1b and GT1b, constitute more than 90% of gangliosides in the brains of various mammalian species. 26 Depending on the number of sialic acid residues on the inner galactose, gangliosides belong to either b-ganglio-series (GD1b and GT1b) or a-ganglio-series (GM1 and GD1a). 27 Studies of their molecular structures have shown that the number of sugar units and the position and linkage type of sialic acids distinguish each ganglioside 28 and affect their physicochemical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Gangliosides are sialic acid-containing glycosphingolipids that are constituents of mammalian cell membranes, particularly abundant in neuronal cell membranes, and participate in various cellular events of the nervous system (Derry and Wolfe, 1967). GM1, GD1a, GD1b, GT1b and GQ1b are major types of gangliosides found in the brain (Dreyfus et al, 1997;Kotani et al, 1993). They are different in the number and sites of sialic acid residues attached to the carbohydrates.…”
Section: Introductionmentioning
confidence: 99%